«The Easter World» of Nicholas II during the Bell for Witte Tolled - Nelly Mikhailovna Tairova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Being in the Crimea on vacation Nicholas II and Empress Aleksandra Fedorovna unexpectedly for themselves have faced a set of problems: a disease of the tsar and fight for his life, manifestation of the power and firmness from the Empress, the solution of a question of a succession to the throne, devotion and treachery of ministers. In absolutely other foreshortening, the Yalta incident was considered by S.Yu. Witte: the fatal disease of the tsar was meant as a usual diphtheria, but not a typhoid, in a question of a succession to the throne defended the candidate for the male line - grand prince Mikhail Aleksandrovich. Witte has suggested solving at a meeting of ministers this problem based on the legislation, but not at the request of the Empress. From this point position of the most successful minister in the Government Nicholas II has reeled. A consequence of a disease of the Emperor the habitual amplitude of the relations has begun to fluctuate - from disappointment to mistrust and secret desire to dismiss Witte.